IMPLEMENTASI HADIS SEBAGAI NILAI ETIKA DAN MORAL DALAM BERINTERAKSI DENGAN SESAMA MANUSIA DALAM KEHIDUPAN SEHARI-HARI - Suci Ramadhini; Imsar Imsar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the role of hadith as a source of moral guidance in everyday life and its impact on ethics and human behavior in social interactions. As the second primary source of Islamic teachings after the Qur’an, hadith contains essential ethical values such as honesty, compassion, and justice, which serve as guidelines for individuals in conducting themselves within society. Utilizing a qualitative descriptive approach, this research analyzes authentic hadiths and supporting literature to identify and comprehend the moral values embedded within them. The findings demonstrate that applying these values, such as mutual respect and cooperation, contributes to improving the quality of social interactions and strengthening community solidarity. Furthermore, the study provides deeper insights into how hadith encourages individuals to act more ethically in various contexts, including family, workplace, and community settings. Therefore, hadith functions not only as a spiritual reference but also as a strong ethical foundation for shaping human behavior.